Free-Living Aquatic Turtles as Sentinels of Salmonella spp. for Water Bodies - Hernandez, Sonia M.; Maurer, John J.; Yabsley, Michael J.; Peters, Valerie E.; Presotto, Andrea; Murray, Maureen H.; Curry, Shannon; Sanchez, Susan; Gerner-Smidt, Peter; Hise, Kelley; Huang, Joyce; Johnson, Kasey; et al. (Frontiers in Veterinary Science, 2021)
Reptile-associated human salmonellosis cases have increased recently in the United States. It is not uncommon to find healthy chelonians shedding Salmonella enterica, but the rate and frequency of bacterial shedding are not fully understood, and most studies have focused on captive, vs. free-living chelonians and often, in reaction to an outbreak, vs. to understand their ecology and significance as sentinels. In this study, we surveyed free-living aquatic turtles from Georgia (USA) to determine the prevalence of Salmonella shedding and assess the importance of species, basking ecology, demographics, season, and landcover on shedding. We also assessed genetic relatedness between human and turtle isolates, plus other animal and water isolates reported from our study area. We isolated Salmonella from 45 of 194 turtles (23.2%) across six species. Prevalence was higher in juveniles (30%) than adults (17%) and higher in bottom-dwelling species (31%; i.e., common and loggerhead musk turtles, snapping turtles) than basking species (15%; i.e., sliders, painted turtles). Salmonella prevalence decreased as forest cover, canopy cover, and distance from roads increased, and rates were higher in low-density residential areas. We isolated common reptile-associated serovars, but also several serovars not typically reported for turtles (e.g., S. Montevideo, S. Newport). Importantly, 85% of the turtle isolates matched PulseNet PFGE patterns of Salmonella isolates from humans, including within Georgia. Fewer water isolates overlapped with human cases, perhaps due to bacterial dilution. Collectively, our results suggest that turtles accumulate Salmonella in water bodies and they may be effective sentinels of environmental contamination. Ultimately, the prevalence rates we found in wild aquatic turtles, along with the genetic relationship of turtle to human isolates, also highlight concerns about public health.